Pendampingan Kegiatan Ekstrakurikuler Pramuka Terhadap Pembentukan Karakter Siswa di MIS Fathul Iman Melalui Pengabdian Mahasiswa IAIN Palangka Raya - Nurlaila Nurlaila; Sulistyowati Sulistyowati; Arif Rahman (Jurnal Pengabdian Masyarakat Indonesia (JPMI), 2024)
Scouting, which means Young Praja, is a non-formal education movement that aims to develop various aspects of personality, physical, mental, social and spiritual.  Forming student character is the main goal of Indonesian national education. Character education can be implemented through various activities, one of which is through extracurricular activities, where Scouts play an important role in educating the younger generation with the values ​​of honesty, discipline, cooperation, responsibility and leadership. At MIS Fathul Iman, mentoring by IAIN Palangka Raya students in Scouting activities aims to strengthen students' understanding of these values. This research uses qualitative data methods obtained through observation and documentation. The results show that Scout activities, through activities such as making group chants, encourage students to cooperate, discipline, responsibility and creativity, as well as increase their self-confidence but also build solidarity and a sense of togetherness. It is hoped that this research will provide insight into the development of more effective service programs in the context of character education in the future. Keywords: Students, Character Building, Scout Extracurricular